Knowledge Sharing in Organizations: Multiple Networks, Multiple Phases - Hansen, Morten T.; Mors, Marie Louise; Løvås, Bjørn (Academy of Management Journal, 2005)
Different subsets of social networks may explain knowledge sharing outcomes in different ways. One subset may counteract another subset, and one subset may explain one outcome but not another. We found support for these arguments in an analysis of a sample of 121 new-product development teams. Within-team and interunit networks had different effects on the outcomes of three knowledge-sharing phases: deciding whether to seek knowledge across subunits, search costs, and costs of transfers. These results suggest that research on knowledge sharing can be advanced by studying how multiple networks affect various phases of knowledge sharing.